Pelatihan Membuat Kuis dengan Aplikasi Quizizz pada Guru SMP Se Kabupaten Bireun - Yuli Astuti (Jurnal Pengabdian Dian Mandala, 2023)
Teachers as facilitators are required to be able to operate technology. In this modern era, there are many applications that teachers can use in classroom learning. The Quizizz application is an application that is very easy to understand to help teachers present and evaluate lesson material. Observation results show that the majority of junior high school teachers in Bireun Regency have never used the Quizizz application in learning. The methods used in training include lecture, question and answer and demonstration methods. The results of the implementation show an increase in teacher understanding in operating the Quizizz application.